(untitled) (Journal of Business and Technology (Dhaka), 2017)
The growth of Islamic Finance (IF) is hindered by non-conducive environment globally despite acceptability, efficiency and effectiveness of its products and services. The elements of non-conduciveness are bedded in the accounting methodology, tax- deductibility of interest expenses on bank loans, over-helming use of credit by households, businesses and governments, excessive use of leverage in banks, yielding disproportionately higher ROE (Return on Equity), resulting in global debt trap and extreme inequality in income and wealth distribution. Islamic finance if used properly by reforming the existing financial architecture and regularity environment can provide a sustainable basis for higher economic growth by encouraging private enterprises in Muslim and other countries by reducing deceit and corruption and increasing social capital through building trust. This will make the world a better place for humanity and avoid the impending threats from environmental and manmade disasters. This paper is based on secondary sources of information collected from publications of papers, research monograph, books and authors own works done at Manchester Business School (MBS), Manchester, UK, 1974-77. Journal of Business and Technology (Dhaka) Vol.11(1-2) 2016; 1-9